In the darkroom - Faludi,Susan (Metropolitan Books/Henry Holt and Company, 2016)
A NEW YORK TIMES BOOK OF THE YEAR WINNER OF THE KIRKUS PRIZE SHORTLISTED FOR THE PULITZER PRIZE 2017 From the Pulitzer Prize-winning journalist and best-selling author of `Backlash', an astonishing confrontation with the enigma of her father and the larger riddle of identity.